2D DIGE based proteomics study of erythrocyte cytosol in sickle cell disease: Altered proteostasis and oxidative stress. Issue 21 (1st October 2013) - Basu, Avik; Saha, Sutapa; Karmakar, Shilpita; Chakravarty, Sudipa; Banerjee, Debasis; Dash, Bisnu Prasad; Chakrabarti, Abhijit
Abstract : Sickle cell disease (SCD) is a hemolytic disorder caused by a mutation in beta‐globin gene and affects millions of people worldwide. Though clinical manifestations of the disease are quite heterogeneous, many of them occur due to erythrocyte sickling at reduced oxygen concentration and vascular occlusion mediated via blood cell adhesion to the vessel wall. We have followed proteomic approach to resolve the differentially regulated proteins of erythrocyte cytosol. The deregulated proteins mainly fall in the group of chaperone proteins such as heat shock protein 70, alpha hemoglobin stabilizing protein, and redox regulators such as aldehyde dehydrogenase and peroxiredoxin‐2 proteoforms. Proteasomal subunits are found to be upregulated and phospho‐catalase level also got altered. Severe oxidative stress inside erythrocyte is evident from the ROS analysis and Oxyblot TM experiments. Peroxiredoxin‐2 shows significant dimerization in the SCD patients, a hallmark of oxidative stress inside erythrocytes. One interesting fact is that most of the differentially regulated proteins are also common for hemoglobinopathies such as Eβ thalassemia. These could provide important clues in understanding the pathophysiology of SCD and lead us to better patient management in the future.